Performance of foliar nitrogen application in corn crops: Efficiency and physiological response (Research, Society and Development, 2025)
Corn (Zea mays L.) is one of the main agricultural crops in Brazil, with high economic and strategic importance for food security and the livestock and industrial production chains. Despite genetic and management advances, mineral nutrition, especially nitrogen fertilization, still represents a challenge to achieve high productivity. Nitrogen (N) is an essential macronutrient, actively participating in photosynthesis, vegetative growth and grain formation. In this context, foliar fertilization emerges as a complementary alternative to soil application, enabling rapid physiological responses, especially in conditions of root limitation. This literature review aims to analyze and discuss scientific evidence on the effects of foliar application of nitrogen in corn crops, with an emphasis on physiological responses and impacts on productivity. Evidence shows that foliar application of N, especially in the form of soluble urea, improves agronomic attributes such as plant height, leaf area, biomass accumulation and grain yield. It is concluded that, when used strategically, foliar fertilization with nitrogen can contribute to greater efficiency in the use of the nutrient and increased corn productivity, being a valuable tool in the nutritional management of the crop.